On Saturation of Linear Summation Methods for Fourier Series in the Spaces $S_{φ} ^p$ - Shydlich, A. L. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We consider the problem of the saturation of linear summation methods for Fourier series in the spaces $S_{φ} ^p,\; р > 0$. We show that the saturation of a linear method and the saturation order are independent of the parameters $X, ϕ$, and p that define the space $S_{φ} ^p(X)$.